24.3k views
5 votes
Solve for y: y^3+5y^2−9y−45=0

User Yuanzz
by
5.9k points

1 Answer

5 votes

For this, I will be factoring by grouping to solve for y.

Firstly, factor y^3 + 5y^2 and -9y - 45 separately, Make sure that they have the same quantity on the inside:


y^2(y+5)-9(y+5)=0

Now you can rewrite it as
(y^2-9)(y+5)=0 . However we are not finished factoring.

Now with y^2 - 9, we will apply the difference of squares rule, which is
x^2-y^2=(x+y)(x-y) . Apply it as such:


(y+3)(y-3)(y+5)=0

Now that it is completely factored, we can apply the Zero Product Property and solve for y:


y+3=0\\y=-3\\\\y-3=0\\y=3\\\\y+5=0\\y=-5

In short, y = -5, -3, and 3.

User Vahancho
by
5.7k points